A Cognitive Linguistics Study to Reveal the Concept of Death of Indonesian Indigenous Tribe - Nirwanto Maruf; Rita Tanduk (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Despite of many previous studies related to conceptual metaphor have been conducted since George Lakoff and Mark Johnson have introduced their work known as Metaphor We Live By in 1980, but none of them have analysed oral discourse as their corpus. This study aims to reveal the concept of death belonging to one of the Indonesian indigenous tribes located in Sulawesi Island called Kajang tribe. The Kajang tribe has an ancient oral discourse which delivers orally from generation to generation known as Pasang ri Kajang, and it is full of metaphorical expressions. This present study employs the conceptual metaphor theory (CMT) introduced by Lakoff and Johnson (1980, 2003), and the approach of conceptual metaphor analysis (CMA) by Charteris Black (2004) to reveal the concept of death found in Pasang ri Kajang. This qualitative research obtained the data through semi-structured interviews, field observation, recording, and note-taking. The conceptual metaphor techniques comprising three CMA stages, namely identification, interpretation, and explanation, were used for data analysis. The results of the study indicate that the concept of death as found in Pasang ri Kajang is DEATH IS A JOURNEY. This conceptual metaphor gives a detailed description of death as a journey of the soul to the hereafter. This research concludes that people of Kajang believes only good souls are rewarded with eternal life (Karakkang) and extraordinary wealth (Kalumannyang kaluppepeang) in the hereafter (ahera).